(untitled) (Hekima Review, 2013)
Jesus Christ our Lord is Truth, Beauty and Goodness Incarnate. Living completely and faithfully in Him, we encounter, especially through the sacred lit-urgy, the True, the Beautiful and the Good of Christ in the Church. Living in Christ, we live in communion with each member of the Church, in every part of the world and in every period of time. These Truth, Beauty and Goodness of Christ translate, in its entirety, the Love of Christ for us. Thus, as we encounter Christ at Mass and in our fellow human beings, we intently desire to offer to Him our worship; we wish to give glory to Him by the best means at our disposition. Hence, for the Church, beauty is manifested most fully and perfectly in the sacred liturgy, in the sacramental encounter with the living Christ who dwells within the Church through the outpouring of the Holy Spirit. We are therefore encouraged to celebrate the sacred liturgy with our gaze fixed on God within the communion of saints, the living Church of every time and place so that it will truly be an expression of the sublime beauty of the God who has called men and women to be his friends. It is indeed our call as Christians to always celebrate our faith with others.